Experimental Research on Mechanical and Permeability Properties of Nylon Fiber Reinforced Recycled Aggregate Concrete with Mineral Admixture - Jawad Ahmad; Osama Zaid; Carlos López-Colina Pérez; Rebeca Martínez-García; Fernando López-Gayarre (Applied Sciences, 2022)
Plain concrete’s major two drawbacks are its low tensile strength and high carbon footprint. Joint adding of fibers and recycled/waste materials in concrete might assist to resolve these problems. In the present study, a novel technique is planned to improve the recycled aggregate concrete (RAC) mechanical behavior and durability performance by joint incorporation of silica fume (SF) and nylon fibers (NF). In this research paper, different properties of concrete samples are examined for example flexural strength, compressive strength, split tensile strength, penetration of chloride ions, acid resistance, and water absorption. It was noted that adding nylon fibers as individual components enhances the recycled aggregate concrete mechanical characteristics and resistance to acid exposure. The inclusion of nylon fibers improved the behavior of the recycled aggregate concrete; however, it also increased the chloride penetration and water absorption by only 18% and 8% respectively. Up to 26% of mechanical strength of concrete was improved when silica fume was added in comparison to reference concrete, silica fume also assisted in controlling the loss of durability because of adding recycled aggregate concrete and nylon fibers. Silica fume improved the bond between binder matrix and nylon fibers. The study revealed that the combination of 50% RCA, 0.5% nylon fibers and 20% silica fume are optimum for the joint incorporation into concrete that can assist in developing sustainable, durable, and ductile recycled aggregate fiber reinforced concrete.